Handbook of IoT and blockchain : methods, solutions, and recent advancements - Mishra, Brojo Kishore, 1979-; Kuanar, Sanjay Kumar; Peng, Sheng-Lung; Dasig, Daniel D., Jr. (Boca Raton, FL : CRC Press, 2020)
"This handbook includes contributions from around the globe on recent advances and findings in the domain of Internet of Things (IoT) and Blockchain. Chapters will include theoretical analysis, practical implications and extensive surveys with analysis, on methods, algorithms, and processes, for new product development. IoT and Blockchain are the emerging topics in the current manufacturing scenario. This handbook will include recent advances, showcase the work of researchers around the globe, offer theoretical analysis and practical implication, present extensive surveys with analysis, new contributions and proposals on methods, algorithms, and process, and also provide recent advances on both quantitative and qualitative articles, case studies, conceptual works and theoretical backing. This handbook will be of interest to graduate students, researchers, academicians, institutions, and professionals that are interested in exploring the areas of IoT and Blockchain"--
OCLC-licensed vendor bibliographic record.
Keywords: Blockchains (Databases); Internet of things; COMPUTERS / Database Management / Data Mining; TECHNOLOGY / Engineering / General; TECHNOLOGY / Manufacturing